Usefulness as a tool for measuring the implementation of the strategy of selected Pomeranian cities in terms of increasing residents' satisfaction with the availability and quality of public services - Kałaska, Agnieszka; Kępa, Paweł; Skelnik, Klaudia; Zakrzewska, Sylwia (Polityka i Społeczeństwo, 2023)
Urban development strategies indicate the directions of activities of local authorities aimed at improving the quality of life of residents. The factors influencing the satisfac- tion of residents were presented using indicators in the aspect of three orders: social, economic and environmental. The study of the quality of life of residents, using measurable and verbal factors, allows to present a clear and legible developmental picture.